2023
DOI: 10.3390/nu15061434
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed Ratios between Essential and Toxic Trace Elements as Potential Biomarkers of Acute Ischemic Stroke

Abstract: Background: Cadmium (Cd) and lead (Pb) are known to be two of the metal contaminants that pose the greatest potential threat to human health. The purpose of this research study was to compare the levels of toxic metals (Cd, Pb) in patients with acute ischemic stroke (AIS), with a control group in Podlaskie Voivodeship, Poland. The study also aimed to assess the correlations between toxic metals and clinical data in AIS patients, and to assess the potential effect of smoking. Materials and methods: The levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…Regarding the Podlaskie Voivodeship region in Poland, comprehensive examinations analyzing toxic metals in AIS patients appear scant. Our current findings underline the critical public health ramifications, spotlighting a notable trace element imbalance in acute ischemic stroke patients [18]. Of notable significance from our study was the discovery that even at moderately low exposure levels, elevated blood Cd concentrations substantially influence ischemic stroke onset.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Regarding the Podlaskie Voivodeship region in Poland, comprehensive examinations analyzing toxic metals in AIS patients appear scant. Our current findings underline the critical public health ramifications, spotlighting a notable trace element imbalance in acute ischemic stroke patients [18]. Of notable significance from our study was the discovery that even at moderately low exposure levels, elevated blood Cd concentrations substantially influence ischemic stroke onset.…”
Section: Introductionmentioning
confidence: 52%
“…Research is increasingly showcasing heavy metal exposure as a potential stroke risk factor, with emerging studies linking elevated blood-Cd levels to higher stroke occurrences. A recent systematic review and meta-analysis even suggest chronic exposure to metals like Pb, Cd, and Cu might elevate stroke risk [18].…”
Section: Introductionmentioning
confidence: 99%
“…Many risk factors, including smoking and hepatic, renal, cardiovascular, and DM illnesses, can raise the body's levels of elements. A diagnostic for prolonged exposure, an increase in blood trace element values revealed the body's stress [17,18]. The best way to determine the exposure to hazardous elements (like Lead) that cling tightly to intracellular proteins is to analyze serum [19,20].…”
Section: Radiography Workers Control Groupmentioning
confidence: 99%
“…Importantly, we also found that AF/AFL mortality and DALYs attributable to lead exposure are on the rise in low-and low-middle-SDI countries for both male and female populations. Previous studies determined that lead exposure was strongly associated with hypertension [23], acute ischemic stroke [24], and heart failure [25], and that reducing lead exposure can result in substantial advantages for the adult population [26]. Lead exposure should be a prioritised topic, especially in nations and regions with a low or low-middle SDI.…”
Section: Additional Materialsmentioning
confidence: 99%